TRANSPORTASI DAN TRANSFORMASI DATA TERJADWAL DENGAN MENGGUNAKAN SSIS (SQL SERVER INTEGRATION SERVICE) - Banni Satria Andoko (Faculty of Engineering, Universitas Negeri Yogyakarta, 2011)
ABSTRACTNowadays, the Information Systems has become large and distributed. The need of data has become very complex and difficult to provide. In accordence with the distributed system concept, an Information System consists of applications that have their own database and system.State Polytechnic of Malang is Polytechnic that have many major and concentration . Therefore they are using Information System to support their Bussiness Rule. Based on this issue, then we must have a system that can communicate application or system to another application or system.To facilitate the communicationbetween two applications or systems, it needs a service that can provide data exaclty when needed. SSIS(Sql Server Integration Service) is one of many solutions that we can use. Because of its performance and compactness with MsSQL server, it makes it valuable and applicable. Keywords: Data Migration, ETL, MsSQL 2008, RDBMS, SSIS, SQL Query.